Ta’widh in Non-Debt Banking Products: A Study on Islamic Banks in Indonesia - Hidayat, Muhammad Rifqi; Mumtazah, Fitria (Al-Iqtishadiyah: Ekonomi Syariah dan Hukum Ekonomi Syariah, 2024)
The purpose of this research is to examine the imposition of sanctions for customers on sharia term savings products, and to analyze them based on the 43rd fatwa of the National Sharia Council on Compensation (Ta'widh). This is a qualitative field research conducted to five Islamic banks in Indonesia, using inductive-interpretive analysis techniques. The data in this research the research are collected through interviews with the bank, direct observation to the bank, and study of documents through brochures and the bank's official website. The results of the research show that the five banks that are the subject of this research impose administrative fee sanctions for customers who close their accounts before the time period expires, and two of them also impose penalty fees for customers who are late in making deposits. This sanction arises if the customer breaches the contract, and because there are three banks of which suffer losses due to having to pay premiums for free insurance facilities for customers in the product. The costs of these two sanctions have been set by the bank since the beginning of the contract, and the bank will recognize it as profit. The results of the analysis show that only two of the ten provisions of the 43rd DSN fatwa were fulfilled by the five banks, and there were four provisions that the five banks could not fulfill. So we proposes that the sanctions for customers who delay deposits are set by the bank in the form of fines for social purposes as self-punishment, and that banks state clearly at the beginning of the contract that the free account closing fee only applies to customers who close their accounts according to the agreed time period only.